Rassismus, Immigration und Arbeiterbewegungen in den Vereinigten Staaten - Lüthje, Boy; Scherrer, Christoph (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2003)
The article looks at the new organizing experiences of immigrant and minority workers in the USA, It discusses some central conceptions of current debates on race, ethnic identity, and multiculturalism and their meaning for labor organizing, It retraces the structural dimensions of racial and work-place domination under the labor regime established in the 1930s and 1940s, including a more detailed discussion of the ’political economy’ of racial exclusion practiced by post-war labor unions, It intends to show that overcoming racial and ethnic divisions will remain a fundamental political yardstick against which the real changes in the labor movement will have to be measured - a lesson not only of importance for the USA but for most European countries as well.